Phototherapy Induced Hypocalcaemia in Neonates with Jaundice - KC, Rajesh; Kanodia, Piush (Journal of Nepalgunj Medical College, 2021)
Introduction: Neonatal hyperbilirubinemia is seen mainly in the first week of life and in many of the cases it is only in physiological range which requires no intervention. Approximately 5-10% of them have clinically significant jaundice that requires phototherapy and even exchange transfusion. Phototherapy can produce various adverse effects; hypocalcaemia is one of the lesser known effects. So, estimation of calcium levels before and after phototherapy should be done in neonates with jaundice.Aims: The aim of this study is to determine hypocalcaemia, in neonates receiving phototherapy, by measuring serum calcium levels.Methods: This cross sectional study was conducted, from February 2020 to August 2020, on 50 neonates admitted in Neonatal Intensive Care Unit of Nepalgunj Medical College, Kohalpur with unconjugated hyperbilirubinemia requiring phototherapy. Serum calcium levels were evaluated before and after phototherapy. Neonates were assessed for clinical features of hypocalcaemia i.e. jitteriness, irritability/ excitability and convulsions. Data were analyzed using SPSS version 25.P value